2015
DOI: 10.1007/s11605-014-2685-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Laparoscopic Converted to Open Colectomy on Short-Term and Oncologic Outcomes for Colon Cancer

Abstract: Conversion to open colectomy from an initial laparoscopic approach does not worsen the long-term survival in patients with non-metastatic colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 32 publications
4
41
0
1
Order By: Relevance
“…Based on the in- and exclusion criteria, all articles were subsequently selected on title, abstract and full-text. Eventually, 18 studies were selected for inclusion in this review: 12 prospective[ 12 , 15 - 17 , 19 - 22 , 24 - 26 , 28 ], five retrospective cohort studies[ 13 , 14 , 18 , 23 , 29 ] and one prospective case-control study[ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the in- and exclusion criteria, all articles were subsequently selected on title, abstract and full-text. Eventually, 18 studies were selected for inclusion in this review: 12 prospective[ 12 , 15 - 17 , 19 - 22 , 24 - 26 , 28 ], five retrospective cohort studies[ 13 , 14 , 18 , 23 , 29 ] and one prospective case-control study[ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included colon as well as rectal cancer patients. Three studies only included colon cancer patients[ 23 , 25 , 29 ] and five only included rectal cancer patients[ 14 , 22 , 26 , 20 , 28 ]. Overall, a total number of 53329 patients were included in all individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…In multivariate analysis, however, only pathologic T4 stage and tumor-positive lymph node ratio > 0.25 were independently associated with OS and DFS. The prospective database study of Li et al showed a similar 5-year DFS and OS in the converted group compared to the laparoscopic completed group and open resection group [35]. It is important to emphasize that pT4 stage was included in all three studies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a similar disease-free survival and overall survival between their laparoscopic, converted, and open colectomy cohorts. 10 Given the small sample size in their analysis, they were likely underpowered to show any difference among their three groups. Additionally, this study included patients from two high-volume institutions in China, which potentially limits the generalizability of these results to the US population.…”
Section: Discussionmentioning
confidence: 99%